Pengaruh Konsentrasi Asam Klorida pada Arang Aktif Kulit Kelapa Muda untuk Menurunkan BOD dan DO Limbah Cair Tahu - Sumardiyono Sumardiyono; Soebiyanto Soebiyanto (Biomedika, 2019)
Research had been conducted on making activated charcoal from young coconut skin with hydrochloric acid as an activator which would be used as an adsorbent in tofu liquid waste. The making of the adsorbent from young coconut skin was continued by testing its ability to adsorb BOD and DO in tofu liquid waste. Making activated carbon from young coconut skin was done through the selection of washing, drying, drying, activation using hydrochloric acid with immersion time variables. Titration method was used to test the BOD and DO.Concentration of hydrochloric acid used 0.5 N; 1 N; 1.5 N; 2N; and 2.5 N with immersion times of each concentration of 0.5 hours, 1 hour, 1.5 hours, 2 hours and 2.5 hours. Activated charcoal then was used to absorb tofu liquid waste. From the experiment the best results were obtained at a concentration of 2.5 N. For 0.5 hour immersion time, DO was 2013 mg / l with efficiency 86.91% and the BOD was 284 mg / l with efficiency 87.64%. For the 1 hour immersion time, DO was 2015 mg / l with efficiency 87.64% and the BOD was 267 mg / l with efficiency 88.38%. For 1.5 hours of immersion time DO was 2002 mg / l with efficiency 86.52% and the amount of BOD was 305 mg / l with efficiency 86.72%. For 2 hours immersion time DO was 1833 mg / l with efficiency 86.25% and the amount of BOD was 314 mg / l with efficiency 86.33%. For the immersion time of 2.5 hours the DO amount was 1971 mg / l with efficiency 86.17% and the amount of BOD was 313 mg / l with efficiency 86.37%. so it can be concluded that the best BOD results are at 2.5 N hydrochloric acid concentration with 1 hour immersion time, BOD size 267 mg / l with an efficiency of 88.38%, and DO size 2.5 N hydrochloric acid concentration 1 hour immersion time DO amount was 2015 mg / l with efficiency of 87.64%